Causal relationship between inflammatory cytokines and posttraumatic stress disorder: a Mendelian randomization study and potential mechanism analysis - Yingchong Li; Bangliang Xu; Zhitao Chen (European Journal of Psychotraumatology)
Background: Post-traumatic stress disorder (PTSD) is a complex condition linked to inflammation. The causality between inflammatory cytokines and PTSD risk remains unclear.Methods: We conducted a bidirectional two-sample Mendelian randomization (MR) study using genome-wide association study (GWAS) data from 41 inflammatory cytokines and PTSD. Additional analyses included differential gene expression, protein–protein interaction, and functional enrichment to explore underlying mechanisms.Results: MR analysis indicated that higher levels of stem cell factor (SCF) and interleukin-4 (IL-4) are associated with a reduced risk of PTSD. Genes POGZ and LRIG2 were identified as mediators, implicated in the TGF-beta signalling pathway.Conclusion: Our findings suggest a protective role of certain cytokines against PTSD and highlight potential molecular mediators. This knowledge could inform future therapeutic strategies for PTSD.